Efektivitas Pelepah Pinang (Areca catechu) dan Ampas Tebu (Saccharum officinarum) dalam Pembuatan Bio-Styrofoam - Keisha Aulia Saabira; Kireina Yuda Malika; Susanti Rahayu; Arifin Aji Nugroho (Jurnal Integrasi Sains dan Quran, 2025)
The use of disposable styrofoam has become popular due to its practicality, but its use is harmful to health and the environment. Styrofoam, which is made from expanded polystyrene, contains harmful substances such as benzene and styrene, and takes millions of years to decompose and often leaves behind microplastics. As an alternative, making bio-styrofoam from bagasse and areca nut fronds can be an environmentally friendly solution. This research aims to make environmentally friendly bio-styrofoam by utilizing bagasse and areca nut fronds as an effort to reduce agricultural waste while reducing the use of plastic-based styrofoam, which has a negative impact on the environment. Bagasse contains 24% lignin, 53% cellulose, and 20% hemicellulose, while areca nut fronds contain 32% cellulose, 34% hemicellulose, and 17% lignin. Both materials have great potential in making bio-styrofoam. This research uses a qualitative descriptive method, data collection is done by observation and literature study. The results of the water absorption test amounted to 17.9%, the biodegradability test amounted to 50.7% within 2 weeks, and the tensile strength test amounted to 2.30N/mm2, the value has met SNI.